(untitled) (Perner’s Contacts, 2011)
The article presents the results of video analysis performed on selected pedestrian crossings in the Czech Republic. This paper was prepared with financial support for research and development project No. CG911-008-910 "Influence of structural elements geometry on safety and fluency of operation on roundabouts and possibility of rise crashes prediction”, the Ministry of Transport.